Dual band monopole antenna with harmonic suppression capability - Abdullah, Muhammad Zulkarnain (2018)
Growing communication industry have overstated the demand for high performance multi-purpose antenna systems. Monopole antenna are well known for their compact size and low profile applications. The use of GSM and the ISM band frequencies at the same lime by different devices require multiple antenna to support more than two frequencies. Thus this states the requirement and demand for antenna with multiple frequencies of operation and capability. However different dual band antennas also suffer from harmonic generation and higher order resonances. Due to these higher order resonances electromagnetic interference and noise increases and thus they bring down the performance of communication systems. In order to address the problem this research proposes a dual band operation with a Monopole antenna for GSM and ISM band of operation. The antenna resonates at 0.9 MHz for GSM band and 2.4 GHz for ISM band. The antenna was simulated using CST MWS. The proposed antenna was having a dual band operation with harmonics in the higher order bands. In order to reduce the harmonic of the antenna. The stub loaded feed line was proposed. Three different length stubs were attached with the antenna feed line in order to suppress the harmonics on the patch antenna. A thorough investigation was carried out for the harmonic suppression below - 10 dB level. The antenna was fabricated above FR-4 based epoxy substrate material. Scattering parameter measurements were performed using vector network analyzer. The comparison of results shows a good agreement between the measured and the simulated results. It has been demonstrated that the proposed antenna design configuration shows dual resonance at 0.9 and 2.40 GHz for GSM and ISM bands at total efficiencies above 80%. Moreover, the application of stubs attached to the feed line the harmonics suppression has been achieved below -10 for the frequency band of 3 -10 GHz.